Post-acquisition organizational and portfolio restructuring and performance: Empirical evidence of acquired companies in the Republic of Serbia - Savović, Slađana D (Industrija, 2016)
This paper examines the impact of post-acquisition restructuring on performance, based on a sample of Serbian acquired companies during the period 2002-2011. Using exploratory factor analysis, two new factors of post-acquisition restructuring on performance were identified: the first one refers to organizational restructuring, and the second factor refers to portfolio restructuring (divestitures). By using multiple regression analysis, we tested the impact of organizational and portfolio restructuring on post-acquisition performance. The results of analysis indicate that organizational and portfolio restructuring do not have statistically significant impact on post-acquisition performance. Additionally, the results have shown that there are statistically significant differences on implemented activities of organizational restructuring between manufacturing and service sectors. Organizational restructuring was implemented to a greater extent in companies belonging to manufacturing sector than in companies belonging to service sector.